Antecedents of Halal Food Purchase Intention on Young Muslim Consumers - Hantiko Syahid Faruqi Subechan (Faculty of Economics and Business, Jenderal Soedirman University, 2021)
This research is conducted to analyze the antecedents of halal food purchase intention on young Muslim consumers in Purwokerto. The research aims to see whether halal knowledge, attitude, subjective norm, perceived behavioral control, and religiosity has positive effect on purchase intention. 96 respondents became the samples of this research using Purposive Sampling. The regression analysis is used as analytical tools to analyze the data. Based on the result of this research, by using the value of t-statistic of regression analysis it can be concluded that: 1) Halal knowledge has no effect on purchase intention with t-statistic value of 0.914, 2) Attitude has positive effect on purchase with t-statistic value of 3.812, 3) Subjective norm has positive effect on purchase intention with t-statistic value of 2.072, 4) Perceived behavioral control has no effect on purchase intention with t-statistic value of -1.916, 5) Religiosity has positive effect on purchase intention with t-statistic value of 3.037.